Strategi Ekspor Pisang Mas Kabupaten Tanggamus - Rakhmadi, Roby; Luerdi, Luerdi; Fitria , Arie (Gapenas Publisher, 2025)
This article aims to comprehensively examine the export potential of Pisang Mas from Tanggamus Regency to the global market. This research was conducted by identifying production capacity, analyzing the readiness of the supply chain and supporting infrastructure, and evaluating opportunities and challenges in penetrating the international market. The research methodology used is a qualitative approach with a literature study. Data were obtained through export-import statistical reports, scientific journals, and data from international trade bodies such as the ITC and FAO. A value chain analysis was conducted to map the stages of production to effective and efficient distribution. The results show that Pisang Mas Tanggamus has a competitive advantage in terms of taste and visual appearance that are in demand by international consumers but faces challenges such as limited logistics infrastructure, unmet quality standards and international certification, low export literacy among farmers and dependence on the domestic market. The conclusion of this study states that the development of Pisang Mas exports from Tanggamus Regency has great potential and is feasible with strengthening the production system, improving quality, and active involvement of stakeholders. This effort is expected to provide a significant economic impact for local farmers, strengthen Indonesia's position in the global horticultural market and contribute to increasing the country's foreign exchange.